2007
DOI: 10.1152/ajpcell.00043.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial alterations in human gastric carcinoma cell line

Abstract: We compared mitochondrial function, morphology, and proteome in the rat normal gastric cell line RGM-1 and the human gastric cancer cell line AGS. Total numbers and cross-sectional sizes of mitochondria were smaller in AGS cells. Mitochondria in AGS cells were deformed and consumed less oxygen. Confocal microscopy indicated that the mitochondrial inner membrane potential was hyperpolarized and the mitochondrial Ca 2ϩ concentration was elevated in AGS cells. Interestingly, two-dimensional electrophoresis proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 79 publications
4
34
0
Order By: Relevance
“…In our previous study, relatively greater DW m and [Ca 21 ] M were found in a human gastric cancer cell line compared with that in normal cells. 35 Consistently, in this study, the KMS20 cells, having greater DW m , exhibited more robust resistance to bortezomib treatment. In addition, when bortezomib was combined with FCCP, which induces dissipation of DW m , bortezomib resistance was overcome in KMS20 cells (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…In our previous study, relatively greater DW m and [Ca 21 ] M were found in a human gastric cancer cell line compared with that in normal cells. 35 Consistently, in this study, the KMS20 cells, having greater DW m , exhibited more robust resistance to bortezomib treatment. In addition, when bortezomib was combined with FCCP, which induces dissipation of DW m , bortezomib resistance was overcome in KMS20 cells (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Notably, in agreement with our results, the genes encoding adenylate kinase, fructose-bisphosphate aldolase, and the heat-shock protein were also found to be regulated by Ca 2+ ions in E. coli [19]. Surprisingly some of these proteins (adenylate kinase and fructose 1,6-biphosphatase aldolase) have been linked to Ca 2+ regulation in eukaryotic organisms [43][44][45]. For example, the action of the membrane-bound adenylate kinase (AK) in rod outer segments of bovine retina that mediates reactions needed for phototransduction is Ca 2+ -dependent [44].…”
Section: Casupporting
confidence: 91%
“…It is interesting to mention that a genomic analysis of EF-hand related sequences in Arabidopsis found several elongation factors as EF-hand containing proteins [57]. In addition, a 2DE proteomic analysis showed that the synthesis of EF-Tu is affected by Ca 2+ levels [43]. ] i levels have been more frequently studied in E. coli and cyanobacteria [13][14][15]19], limited studies have been done in B. subtilis.…”
Section: Camentioning
confidence: 99%
“…When comparing a human gastric cancer cell line with normal rat gastric mucosal cells, electron microscopy reveals a significant decrease in both the numbers per cell and the size of mitochondria [162]. An ultrastructural study of renal cancer observes most severe mitochondrial aberrations in eosinophilic clear cell renal cell carcinomas, where most mitochondria appear swollen with loose matrix and short attenuated cristae [163].…”
Section: Mitochondrial Morphology Markersmentioning
confidence: 99%